2005
DOI: 10.5194/acpd-5-2427-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol mass closure and reconstruction of the light scattering coefficient over the Eastern Mediterranean Sea during the MINOS campaign

Abstract: Abstract. As part of the Mediterranean Intensive Oxidant Study (MINOS) performed during August 2001 in the Eastern Mediterranean Region, intensive measurements of chemical and radiative properties of atmospheric aerosols were performed at two remote sites on Crete Island, located in the marine boundary layer (MBL), and in the lower free troposphere (FT), respectively. Gravimetric particulate mass, as well as chemically-derived masses of water soluble ions, organic and elemental carbon, and tracer elements for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
28

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 20 publications
4
46
0
28
Order By: Relevance
“…MSE for OM in this study was comparable with those previously reported in fall-winter in China, for example 6.2 m 2 /g in Guangzhou (Tao et al, 2014b) and 6.3 m 2 /g in Shanghai (Cheng et al, 2014), but higher than these previously reported in the summer, such as 4.9 m 2 /g in Guangzhou (Jung et al, 2009) and 4.2 m 2 /g in the Mediterranean (Sciare et al, 2005), and twice as high as the average of 3.1 m 2 /g derived by MLR in the review by Hand and Malm (2007). Our MSE values for AS and AN were comparable with those of 2.8 m 2 /g by Hand and Malm (2007) and 2.4 m 2 /g by Jung et al (2009), but much lower than those of 3.5 m 2 /g for AS and 4.3 m 2 /g for AN by Cheng et al (2014), and 5.3 m 2 /g for AS and 5.5 m 2 /g for AN by Tao et al (2014b).…”
Section: Visibility and Pm 25 Mass Concentrationssupporting
confidence: 90%
“…MSE for OM in this study was comparable with those previously reported in fall-winter in China, for example 6.2 m 2 /g in Guangzhou (Tao et al, 2014b) and 6.3 m 2 /g in Shanghai (Cheng et al, 2014), but higher than these previously reported in the summer, such as 4.9 m 2 /g in Guangzhou (Jung et al, 2009) and 4.2 m 2 /g in the Mediterranean (Sciare et al, 2005), and twice as high as the average of 3.1 m 2 /g derived by MLR in the review by Hand and Malm (2007). Our MSE values for AS and AN were comparable with those of 2.8 m 2 /g by Hand and Malm (2007) and 2.4 m 2 /g by Jung et al (2009), but much lower than those of 3.5 m 2 /g for AS and 4.3 m 2 /g for AN by Cheng et al (2014), and 5.3 m 2 /g for AS and 5.5 m 2 /g for AN by Tao et al (2014b).…”
Section: Visibility and Pm 25 Mass Concentrationssupporting
confidence: 90%
“…Samples were collected within two size fractions [fine mode with aerodynamic diameter (AD) < 2 µm and coarse mode with AD > 2 µm]. Mass concentration [particulate matter (PM)] determined by gravimetric measurements and chemical analyses of the major aerosol components (ions, carbon, crustals) were performed in these two size fractions using the sampling and analytical protocols reported by Sciare et al (2005). Ammonium nitrate and ammonium sulfate were shown to represent on average 50% of PM in the fine mode, the rest being composed of carbonaceous material (black carbon and organic matter) for approximately 40% and sea salt and crustal material for less than 10%.…”
Section: Parisfog: Over 100 Fog and Near-fog Situationsmentioning
confidence: 99%
“…The 50% cut-point diameter (D50) of the 8 µm pore size filter was estimated to be of the order of 1.2±0.1 µm E.A.D. More details can be found in Sciare et al (2005).…”
Section: Aerosol Sampling and Analysismentioning
confidence: 99%
“…For instance nss-SO 2− 4 is mainly present in the aerosol fine mode in contrast to aerosol nitrate, which is confined to coarse mode particles. For a further discussion of the measurements, we refer to Salisbury et al (2003), and Sciare et al (2005). In the following we focus on the gas-aerosol partitioning modeling of reactive nitrogen compounds.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation